2004
DOI: 10.1111/j.1471-4159.2004.02773.x
|View full text |Cite
|
Sign up to set email alerts
|

Variants of TRP ion channel mRNA present in horseshoe crab ventral eye and brain

Abstract: Transient receptor potential (TRP) channels mediate lightinduced Ca 2+ entry and the electrical response in Drosophila photoreceptors. The role of TRP channels in other invertebrate photoreceptors is unknown, particularly those, exemplified by Limulus ventral eye photoreceptors, in which calcium release from intracellular stores is prominent. We have amplified cDNA encoding three variants of a Limulus TRP channel. LptrpA and LptrpB encode proteins of 896 and 923 amino acids, differing by a 27 amino acid insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…They were first identified in Drosophila rhabdomeric photoreceptors (Montell and Rubin, 1989;Hardie and Minke, 1992), and TRP channel homologues have also been found in limulus (Bandyopadhyay and Payne, 2004) and squid (Monk et al, 1996) photoreceptor membranes. This suggests that these channels may constitute a common endpoint in phototransduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…They were first identified in Drosophila rhabdomeric photoreceptors (Montell and Rubin, 1989;Hardie and Minke, 1992), and TRP channel homologues have also been found in limulus (Bandyopadhyay and Payne, 2004) and squid (Monk et al, 1996) photoreceptor membranes. This suggests that these channels may constitute a common endpoint in phototransduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the electrophysiological evidence mentioned above, a cGMP-gated cation channel homologous to the vertebrate CNG channels has been cloned and immunolocalized to the microvillar membrane (Chen et al, 2001). A Limulus trp homolog was also found in the mRNA from the ventral photoreceptor (Bandyopadhyay and Payne, 2004). Finally, the latter authors have found that a DAG analog injected into the cell activated an inward current with properties similar to the light-activated current.…”
Section: Invertebratesmentioning
confidence: 99%
“…These include the heterotrimeric G q protein, phospholipase C (PLCβ4), and in Drosophila , two classes of light-sensitive ‘transient receptor potential’ channels, TRP and TRPL [1820], which admit both Na + and Ca 2+ ions to produce a depolarizing response to light (Figure 3). TRP homologues have also been identified in photoreceptors from the horseshoe crab Limulus [21] and squid [22] and are likely to be a common, and possibly universal feature of rhabdomeric photoreceptors.…”
Section: Transduction In Microvillar Receptorsmentioning
confidence: 99%
“…The IP 3 generated within the lumen of a single microvillus produces a highly localized release of Ca 2+ from an underlying cisterna, raising the Ca 2+ concentration in that microvillus and its immediate neighbors and facilitating the opening of the light-dependent channels by mechanisms that are still not fully resolved [21,23,35,36]. Whether the Ca 2+ comes from inside or outside the cell, it facilitates a rapid and explosive event that is responsible for the quick rise and fall, as well as the large amplitude, of the quantum bump.…”
Section: Microvillar Photoreceptors Respond To Single Photonsmentioning
confidence: 99%